Pathogenesis of Haemorrhagic Septicaemia in Organ Culture, Mice and Calves - Mohamed, Amna Elamin (2007)
Experimental intraperitoneal infection of mice with Pasteurella multocida serotype B:2 at the dose of 107cells caused death in all infected mice between 18 to 24 hours. Microscopy showed suppurative tracheitis. The alveoli lumina were infiltrated with numerous inflammatory cells mainly neutrophils. Pink-stained fibrin and red blood cells were also present in the alveoli lumina. Blue shade of bacterial colonies were observed in the alveolar space and pulmonary vessels. In the aorta, there was degeneration of the endothelium, disruption of the intima and focal myolytic changes in the smooth muscle. In infected mice, scanning electron microcopy (SEM) showed cilial damage and deciliation of tracheal epithelial cells. In the lung extravasation of red blood cells in the alveolar lumina was observed. Rod-shaped bacteria were seen attached to the alveolar wall causing depression on the surfaces of the cells. Changes in the aortas were characterized by rounded endothelial cells. Some rounded endothelial cells were seen about to detach and expelled into the blood vessel lumen. Bacteria were most evident at the intercellular junction of the endothelial cells that were beginning to slough. In infected mice, transmission electron microscopy (TEM) of the trachea showed bacterial cells attached to deformed cilia. Necrotic and apoptotic endothelial cells were seen protruded into the lumen of the affected blood vessel. Several bacteria were attached to the plasma membrane of the endothelial cells and in the blood vessel lumen. Endothelial cells showed electron dense cytoplasmic extensions around the bacteria and as attaching and effacing lesions which were interpreted as the first steps in the phagocytosis process. In the lung, there was thickening of the alveolar septa. Bacteria were seen dividing inside the neutrophils and in the lumen of the blood vessels. Some bacteria were also seen in vacuolated macrophages. Endothelial cells showed apoptosis. Fibrin was present in the alveolar lumina. In the aorta, endothelial cells were fragmented and detached from the basement membranes. Bacteria were attached to the fragmented endothelium. Calves inoculated intranasally with 3.0 x1010 P. multocida serotype B:2 following stressed with dexamethasone developed septicaemia and fibrinous pleuropneumonia. All infected calves died between 24 to 48 hours. Thrombi were observed in the nasal cavity and lung. It is therefore believed that the P. multocida had gained entry into the blood vessel of the nasal cavity and / or lung to various organs causing septicaemia. This is validated by the isolation of pure growth of P. multocida from various congested organs following intranasal infection.